2014
DOI: 10.1111/dme.12590
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and bone turnover markers in a cross‐sectional and prospective study of acute Charcot osteoarthropathy

Abstract: At the onset of acute Charcot foot, serum concentrations of tumour necrosis factor-α and interleukin-6 were elevated; however, there was a significant reduction in these markers at resolution and these markers may be useful in the assessment of disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 24 publications
2
73
2
1
Order By: Relevance
“…OCN is also used as a biomarker of skeletal development, and increased serum OCN level is associated with increased bone mineral density during osteoporosis treatment [48,49]. However, in our study, elevated OCN levels were accompanied by decreased BMD.…”
Section: Discussioncontrasting
confidence: 64%
“…OCN is also used as a biomarker of skeletal development, and increased serum OCN level is associated with increased bone mineral density during osteoporosis treatment [48,49]. However, in our study, elevated OCN levels were accompanied by decreased BMD.…”
Section: Discussioncontrasting
confidence: 64%
“…Petrova et al, have shown that serum C-terminal telopeptide, but not alkaline phosphatase, was signi cantly higher in people with Charcot osteoarthropathy at presentation than in people with diabetes [21]. The observed lack of increased levels of bone alkaline phosphatase in response to the raised Cterminal telopeptide suggests that, in people with Charcot osteoarthropathy, there may be adynamic bone, related to the presence of diabetic neuropathy, which could impair the regulation of bone remodeling [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Petrova et al reported elevation of serum tumor necrosis factor a and interleukin 6 in acute Charcot osteoarthropathy. 12 Baumhauer et al reported the expression of proinflammatory cytokines in bone samples collected during surgery. 3 A review by Adamopoulos and Mellins suggests an alternative pathway for osteoclastogenesis provided by the infiltrating inflammatory …”
Section: Discussionmentioning
confidence: 99%